Development of exact and heuristic optimization methods for safety improvement projects at level crossings under conflicting objectives. (April 2022) - Singh, Prashant; Pasha, Junayed; Moses, Ren; Sobanjo, John; Ozguven, Eren E.; Dulebenets, Maxim A.
Highlights: A new optimization model is proposed for safety improvement projects at level crossings. The multi-objective model directly captures safety and traffic delay perspectives. Exact and heuristic solution approaches are designed to solve the model. A set of computational experiments are conducted for the level crossings in Florida (U.S.). Important managerial insights that would be of interest to railway authorities are shown. Abstract: A significant number of accidents occur each year at level crossings globally. Substantial efforts are being made by different railway authorities and other stakeholders to prevent accidents by installing various countermeasures at level crossings (e.g., mountable curbs, two-quad gates, four-quad gates). However, due to budgetary constraints, it is not possible to deploy countermeasures at all level crossings. Besides, countermeasures have certain effectiveness factors and the associated installation cost. Usually, the cost of the countermeasure increases with its effectiveness. Therefore, it is essential to select the most effective countermeasures at the riskiest level crossings. The implementation of countermeasures at level crossings may lead to certain negative externalities as well. In particular, the deployment of countermeasures can result in a decreased traffic flow, causing traffic delays and adversely affecting the continuity of freight and passenger train movements. This study proposes a multi-objective mathematical model for resource allocation among level crossings, which aims not only to minimize the total hazard severity due to potential accidents but the associated traffic delays as well. Exact and heuristic solution approaches are designed to solve the developed multi-objective model. A set of computational experiments are conducted for the level crossings located in the State of Florida (United States). The results demonstrate superiority of the exact optimization method, as it obtained optimal Pareto Fronts within acceptable computational time. Moreover, a number of sensitivity analyses are conducted to showcase certain managerial insights that would be of interest to railway authorities and other stakeholders involved in level crossing safety improvements.